Fiber-Reinforced Plastics - Alberto Masuelli, Martin (IntechOpen, 2022)
This book deepens the study and knowledge on fiber-reinforced plastics (FRPs), which are composite materials made of a polymer matrix reinforced with fibers. The fibers are usually glass, carbon, or aramid, although other fibers such as paper, wood, or asbestos are sometimes used. The polymer is usually an epoxy, vinyl ester, or polyester thermosetting plastic, and phenol-formaldehyde resins are still in use. Among, the most prominent applications of FRPs are in the aerospace, automotive, marine, and construction industries. The development of FRPs has a very promising future with a marked annual increase and with a wide range of sources. This book presents comprehensive information on FRPs and their wide variety of applications in the industry worldwide.